Pedagogia arteira: autoria pedagógica antirracista na educação infantil - Santos, Sandy Emanuele Sampaio (2025)
Black women exist, they resist and invent other worlds! And when this black woman is a teacher of “little boys” she becomes a crafty black teacher, who, by bending down to listen and speak to black children, learns from them the art of invention and thus her inventions forge new, resistant and creative perspectives of being, belonging and belonging to the world of education that constantly tries to make us invisible. In this sense, the present work aims to: Understand how my writing body-territory forges a Pedagogical Turn as a possibility for the education of ethnic-racial relations in early childhood education. To answer it, it was necessary to highlight the importance of racial literacy for the forging of my body-territory as an anti-racist black teacher of childhoods, in addition to pointing out the dialogue between Decolonial Pedagogy and Arteira Pedagogy created from the Pedagogical Turn and finally presenting the introductory paths of Akilomwana's theoretical-methodological contribution, which points to the possibility of akilombamento among children in early childhood education. The research carried out was qualitative in nature, based on the methodology of Escrevivências by Conceição Evaristo (2005) inspired by the creative and inventive power of Nanã, which is strengthened through the theoretical debate of the bibliographic review centered on the fields of black feminist epistemologies, decoloniality, education of ethnic-racial relations and Afro-Brazilian and African philosophies thinking about black children, their childhoods and anti-racist pedagogical practices, for this, the authors used were: bell hooks (2017; 2020), Paulo Freire (1982; 2003;), Aparecida Ferreira (2019), Eduardo Miranda (2014; 2020), Marta Santos (2008; 2024), Nilma Lino Gomes (2002; 2012), Kabengele Munanga (2005), Catherine Walsh (2006), Renato Noguera (2016; 2019), Fuki-au;Lukondo-Wamba (2000), Azoilda Loretto Trindade (2005). The study highlighted how the pedagogical authorship of a black early childhood teacher can propose fissures in the current order of education, through the ancestral, feminine and decolonial movement of thinking about anti-racist pedagogical practices through art education for early childhood, based on her experiences throughout her educational trajectory.